MEDEIA: RITOS E MAGIA - Cândido, Maria Regina (PHOÎNIX, 2020)
Through Aledeia's mythical narratives we can reach shadows of practices and magic-religious rites which were part of the poliade organization. The Athenian passage rites marked the transition from the youth to adult age. After this ceremony the youth started to occupy their social places and assumed their responsibilities as a palls member.